1987
DOI: 10.1128/jcm.25.1.122-127.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to teichoic acid and peptidoglycan in Staphylococcus aureus osteomyelitis

Abstract: An enzyme-linked immunosorbent assay was used to evaluate the immunoglobulin G (IgG) response to Staphylococcus aureus crude teichoic acid (TA) and peptidoglycan (PG) in both rabbits and patients with osteomyelitis. In rabbits with experimental S. aureus osteomyelitis, elevated levels of IgG to TA were present in 13/18 (72%) of the serum samples obtained at 4 and 10 weeks postinfection. In contrast, only 5/18 (28%) of these sera were found to be positive for antibodies to PG. Of a total of 39 patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[16^19]) but the identity of the immunogens, particularly the protein immunogens, of S. aureus still remain to be de¢ned in detail. Most of the published studies have concluded that both uninfected and infected patients have circulating antibodies to S. aureus although there generally are di¡erences in the antibody titres to the bacterium or selected bacterial components [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…[16^19]) but the identity of the immunogens, particularly the protein immunogens, of S. aureus still remain to be de¢ned in detail. Most of the published studies have concluded that both uninfected and infected patients have circulating antibodies to S. aureus although there generally are di¡erences in the antibody titres to the bacterium or selected bacterial components [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Culture of fluid/pus from sinuses or discharging ulcers is not reliable, thus leading to the dependence of imaging and high suspicion of a surgeon in managing osteomyelitic patients. To determine the causative pathogen implicating in osteomyelitis, a sample of choice is bone fragments because culture of fluid/pus from sinuses or open is always associated with superficial bacteria contaminants [4,5]. This study investigated the pathogens causing osteomyelitis among patients undergoing surgical treatment at Bugando Medical Centre, Mwanza-Tanzania for the purpose of generating data that can be used to devise antibiotic treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with osteomyelitis do not usually have high levels of antibodies to staphylococcal cell wall antigens. A recent study (14) showed that such patients more frequently had antibodies to P-RTA than to PG. This was also the case in our study, although the fractions of positives for both antigens were low, 38 and 19%, respectively.…”
Section: Discussionmentioning
confidence: 99%